2020
DOI: 10.3892/ol.2020.12411
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 expression predicts response to neoadjuvant chemotherapy for locally advanced uterine cervical cancer

Abstract: The standard care for patients with locally advanced cervical cancer is concurrent chemoradiotherapy. Successful neoadjuvant chemotherapy (NAC) can reduce tumor size and enable patients to be eligible for a hysterectomy, which can improve their prognosis. Selecting the right candidate for NAC is important since NAC failure results in switching to radiation therapy and can lead to a worse prognosis due to a delay in the initiation of the core therapy. Therefore, the identification of biomarkers that can predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Previous studies have implicated PRMT1 in various cancers, as it regulates post-translational modifications that are crucial for cancer pathophysiology (27,28). PRMT1 expression can be used to predict the outcomes of neoadjuvant treatments for locally advanced uterine cervical cancer (29). Li et al (30) reported that PRMT1 promoted breast cancer cell proliferation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated PRMT1 in various cancers, as it regulates post-translational modifications that are crucial for cancer pathophysiology (27,28). PRMT1 expression can be used to predict the outcomes of neoadjuvant treatments for locally advanced uterine cervical cancer (29). Li et al (30) reported that PRMT1 promoted breast cancer cell proliferation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…PRMT5 expression is upregulated in cervical cancer and can promote EMT procession, while high levels of PRMT8 expression were also observed in cervical cancer 45 , 46 . It has been reported that PRMT1 expression maybe a potential predictive marker for neoadjuvant chemotherapy treatment in patients with locally advanced cervical cancer 47 . Combination of inhibitors of PRMT1 and PRMT5 has a synergistic cancer cell growth inhibition in pancreatic cancer and DLBCL cell lines and in pancreatic adenocarcinoma xenografts mouse models 48 .…”
Section: Discussionmentioning
confidence: 99%
“…However, reliable and specific biomarkers for the diagnosis and prognosis of cervical cancer are scarce and lack exploration. Earlier research had focused on a single biomarker, which might reduce the prognostic performance 19 21 . Therefore, more reliable prognostic models for CC patients currently are urgently need.…”
Section: Discussionmentioning
confidence: 99%